Self-Compassion dengan Gratitude pada Mahasiswa Tingkat Akhir - Muhammad Firmansah; Timorora Sandha Perdhana (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
College students are often experience unstable physical and emotional conditions including college students who are at the stage of writing their dissertation or thesis. The research aims to investigate the college student’s psychological well-being and gratitude of during working on their thesis. The study was conducted by a quantitative method with a correlation approach, 134 students who were enrolled at a Bhayangkara university and were engaged in the thesis stage, completed an questionnaire about psychological well-being and gratitude. The results showed that there was a significant positive relationship between self-love and gratitude with a correlation coefficient of (0.769) which means that the higher the self-love for final year students, the higher the level of gratitude will be, and vice versa. It is hoped that final year students will care more about themselves so that they have more gratitude.